(3QSGdI aj EKHGJ GdhGLH GdbOjeIs - (3GdUOjbj, GdOhGfj, LdGd GdOjf, eMeO Hf CSYO J (B918 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; SHMGfc SHMGfc eG CYXe TCfc hHYO ajbhd eMeO Hf CSYO GdOhGfj GdUOjbj bO LQOJ aj gPg GdQSGdI hLhg HQGgjf EKHGJ GdhGLHs
(3BNQgG (B:s
(3ZfeG jOd Ydi GdGSJdRGe hOYhi GdVQhQI aj eMd GdefY ZjQ eSehYI hdgPg GdeHGMK eRjO JaUjd QHeG JYKQ aj HYV JYdjbGJfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 32s
(3eYLe GdeDdajf (B3 / 126s
(3cTa GdXfhf (B1 / 842s
(3TPQGJ GdPgH (B8 / 160s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds